Supply chains efficiency increasing based on the modelling of logistics operations. (2017) - Lukinskiy, Valery; Lukinskiy, Vladislav; Merkuryev, Yuri
For evaluating the integrated supply chains' (SCs) effective functioning, some new criteria are frequently used apart from the total logistics costs (TLC). These criteria characterise the quality and reliability of accomplishing logistics operations and functions. It is obvious that these metrics are connected and their separate representation is a consequence of not enough developed supply chains' theoretic model and, accordingly, analytical tools allowing carrying out a comprehensive assessment of these metrics. The paper presents the critical analysis of the existing approaches to the TLC evaluation and SC reliability, the methodical approach which allows evaluating the total costs indexes and supplying chains reliability. This approach includes, firstly, the equation of the total logistics costs; secondly, the reliability evaluation model of a simple supply chain which is a reserved system with a renewal; thirdly, a complex of models for the evaluation of the reliability of basic logistics operations (purchase, order processing, choice of intermediaries, transportation, warehouse placement and storage). As most indicators which describe the chain functioning are random values, to obtain the required evaluations there is a developed algorithm based on simulation.